Fostering Reading Skills through Interactive Media: A Collaborative Learning Perspective Using Liveworksheets - Priska Reski Tiaratna; Muflihah Muflihah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study addresses the persistent challenge of low Arabic reading comprehension (maharah qira’ah) among tenth-grade students at Madrasah Aliyah, a problem rooted in monotonous instructional methods and students’ limited exposure to interactive learning tools. The primary objective of this research is to evaluate the effectiveness of Liveworksheets as an interactive web-based medium in improving students’ Arabic reading skills and to examine student responses toward its implementation. A gap identified in prior studies is that while digital tools have been explored in general Arabic learning, their specific application to developing maharah qira’ah through a collaborative classroom action research design remains underexplored. This study offers a novel contribution by integrating Liveworksheets within a two-cycle Classroom Action Research (CAR) framework following the Kemmis and McTaggart model, employing both qualitative and quantitative approaches. Data were collected through reading comprehension tests, structured classroom observations, and student response questionnaires. Findings demonstrate a significant improvement in classical learning mastery: from 52.7% in the pre-cycle with a mean score of 69.7, rising to 72.2% (mean: 76.6) in Cycle I, and reaching 86.1% (mean: 82.8) in Cycle II, surpassing the minimum classical mastery threshold of 85%. Student engagement, motivation, and confidence also increased substantially across cycles. This research contributes empirical evidence that Liveworksheets, particularly when implemented with a collaborative strategy, constitutes an effective and replicable model for enhancing Arabic reading instruction in Islamic secondary education contexts.